Biosurfactant-Producing Lactobacilli: Screening, Production Profiles, and Effect of Medium Composition - Eduardo J. Gudiña; José A. Teixeira; Lígia R. Rodrigues (Applied and Environmental Soil Science)
Biosurfactant production was screened in four lactobacilli strains. The highest biosurfactant production (excreted and cell-bound biosurfactants) was achieved with Lactobacillus paracasei ssp. paracasei A20, a strain isolated from a Portuguese dairy plant, with a decrease in the surface tension of 6.4 mN m−1 and 22.0 mN m−1, respectively. Biosurfactant production by this strain was evaluated under different culture broth compositions. The use of different nitrogen sources revealed that yeast extract is essential for bacterial growth, while peptone is crucial for biosurfactant synthesis. For biosurfactant production, the use of peptone and meat extract yielded a higher production when compared to the standard medium, with a surface tension reduction of 24.5 mN m−1 Furthermore, experiments were also conducted in a reactor with pH and temperature control. Biomass and biosurfactant production in bioreactor was higher comparing with the experiments conducted in shake flaks. The optimization procedure adopted in the current work was found to improve the biosurfactant production and opened new perspectives for the use of L. paracasei ssp. paracasei A20 as a promising biosurfactant-producer.